2009
DOI: 10.1111/j.1365-2966.2009.15237.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent star-forming activity in local elliptical galaxies

Abstract: The formation and evolution of elliptical galaxies (EGs) are still an open question. In particular, recent observations suggest that EGs are not only simple spheroidal systems of old stars. In this paper, we analyse a sample of EGs selected from the Sloan Digital Sky Survey in order to study the star‐forming activity in local EGs. Among these 487 ellipticals, we find that 13 EGs show unambiguous evidence of recent star formation activity betrayed by conspicuous nebular emission lines. Using the evolutionary st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 97 publications
2
35
0
Order By: Relevance
“…Again all galaxy templates provide an acceptable fit, where the best fit is obtained with an elliptical galaxy. We note that the SFR is in the range of local star-forming elliptical galaxies (Huang & Gu 2009). From the best fit we derive AB absolute magnitudes M B = −19.91 and M K = −20.51, and slight evidence for a dust extinction reddening similar to the SMC with a visual extinction of A host V = 0.7 +0.2 −0.4 .…”
Section: The Host Galaxy Of Grb 090510mentioning
confidence: 93%
“…Again all galaxy templates provide an acceptable fit, where the best fit is obtained with an elliptical galaxy. We note that the SFR is in the range of local star-forming elliptical galaxies (Huang & Gu 2009). From the best fit we derive AB absolute magnitudes M B = −19.91 and M K = −20.51, and slight evidence for a dust extinction reddening similar to the SMC with a visual extinction of A host V = 0.7 +0.2 −0.4 .…”
Section: The Host Galaxy Of Grb 090510mentioning
confidence: 93%
“…Therefore, E+A galaxies have been interpreted as post-starburst galaxies, that is, a galaxy that has experienced a recent starburst, but truncated it suddenly. Some works have been performed on this type of galaxies (Falkenberg et al 2009a,b;Huang & Gu 2009;Pracy et al 2009, and references therein).…”
Section: E+a Galaxiesmentioning
confidence: 99%
“…The presence of a small fraction (∼5.7%) of blue ETGs in the local Universe with estimated star-formation rates (SFRs) between 0.5 and 50 M /yr (Schawinski et al 2009) lends additional support to this notion. That an appreciable fraction of nearby ETGs continues its build-up at a very slow pace, with specific SFRs of < ∼ 10 −11 yr −1 (e.g., Salim et al 2012), is further indicated by multiwavelength studies that combine singlefiber spectroscopy with GALEX/SDSS photometry (e.g., Huang & Gu 2009;Petty et al 2013;Pan et al 2014).…”
Section: Introductionmentioning
confidence: 99%